Myocardial infarction with non-obstructive coronary arteries - Sadowski, Marcin; Rekść, Łukasz; Stępień, Aleksander; Kuchinka, Jakub; Zieliński, Paweł; Grabski, Marek; Ręba, Patrycja; Barańska, Edyta (Medical Studies/Studia Medyczne, 2018)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a working diagnosis in about 10% of cases presenting with symptoms suggestive of acute myocardial ischaemia and no significant atherosclerotic plaques in coronary angiography. It is a heterogenous clinical entity with a complex aetiology and always requires a challenging work-up. The final diagnosis may confirm any coronary pathology (dissection, spasm, thrombus) or significantly differ from the previous one (myocarditis, takotsubo cardiomyopathy). This paper focuses on the current knowledge on MINOCA, guidelines on the management of patients, and indicates new research areas to further elucidate this issue. The most important message is that MINOCA is a serious condition with outcomes at least as serious as in myocardial infarction resulting from coronary atherosclerosis.